F is for fugitive eaudiobook - Grafton, Sue (Kinsey Millhone, 2005)
Everyone knew the kind of girl Jean Timberlake was — ask anybody in the sleepy surf town of Floral Beach and they'd say Jean was wild, looking for trouble. But she certainly wasn't looking for murder. She was found dead on the beach seventeen years ago, and a rowdy ex-boyfriend named Bailey Fowler was convicted of her murder and imprisoned — and then Bailey escaped. Now private eye Kinsey Millhone steps into a case that should have never been closed, in a town where there's no such thing as a private investigation.